Spinal 5-HT1A, not the 5-HT1B or 5-HT3 receptors, mediates descending serotonergic inhibition for late-phase mechanical allodynia of carrageenan-induced peripheral inflammation. (23rd July 2015) - Kim, Joung Min; Jeong, Seong Wook; Yang, Jihoon; Lee, Seong Heon; Kim, Woon Mo; Jeong, Seongtae; Bae, Hong Beom; Yoon, Myung Ha; Choi, Jeong Il
Highlights: Spinal 5-HT has an anti-allodynic effect in late-phase carrageenan inflammation. 5-HT1A receptor is involved in anti-nociceptive processing in spinal cord. Spinal 5-HT1B or 5-HT3 receptor plays a limited role in nociceptive processing. Abstract: Previous electrophysiological studies demonstrated a limited role of 5-hydroxytryptamine 3 receptor (5-HT3R), but facilitatory role of 5-HT1AR and 5-HT1BR in spinal nociceptive processing of carrageenan-induced inflammatory pain. The release of spinal 5-HT was shown to peak in early-phase and return to baseline in late-phase of carrageenan inflammation. We examined the role of the descending serotonergic projections involving 5-HT1AR, 5-HT1BR, and 5-HT3R in mechanical allodynia of early- (first 4 h) and late-phase (24 h after) carrageenan-induced inflammation. Intrathecal administration of 5-HT produced a significant anti-allodynic effect in late-phase, but not in early-phase. Similarly, intrathecal 5-HT1AR agonist (8-OH-DPAT) attenuated the intensity of late-phase allodynia in a dose dependent fashion which was antagonized by 5-HT1AR antagonist (WAY-100635), but produced no effect on the early-phase allodynia. However, other agonists or antagonists of 5-HT1BR (CP-93129, SB-224289) and 5-HT3R (m-CPBG, ondansetron) did not produce any anti- or pro-allodynic effect in both early- and late- phase allodynia. These results suggest that spinal 5-HT1A, but not 5-HT1B or 5-HT3 receptors mediate descending serotonergic inhibition on nociceptive processing of late-phase mechanical allodynia in carrageenan-induced inflammation.